(a)
The inverse is when you swap the variables and solve for y.
g(t) = 2t - 1 (Note: g(t) represents y)
rewrite as: y = 2t - 1
swap the variables: t = 2y - 1
solve for y: t + 1 = 2y
![(t + 1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6ak4htssmm1l4uesydchfuirv7pocfl0fo.png)
= y
Answer for (a):
=
(b)
Same steps as part (a) above:
h(t) = 4t + 3
rewrite as: y = 4t + 3
swap the variables: t = 4y + 3
solve for y:
Answer for (b):
=
![(t - 3)/(4)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/kwhoc36yz827b41s2bbb28l2orbd1w1noj.png)
(c)
![g^(-1) ( h^(-1)(t)) = g^(-1) ((t - 3)/(4))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/j52fei0w5fut3yqaz92701t889fnxrw54x.png)
replace all t's in the
![g^(-1)(t)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/pptkjpena62c204p47c1qidkv5wx6hzwi8.png)
equation with
![g^(-1) ((t - 3)/(4))](https://img.qammunity.org/2019/formulas/mathematics/middle-school/hz4wh56o03ikohm8377uu8dot4ipnn84gu.png)
=
![( (t-3)/(4) + 1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/9dojcpnjwemxd43dvadjwomfolrzx5guvo.png)
=
![( (t-3)/(4) + (4)/(4))/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/cycwswm4tswsi1d0bq9mm824gjgtl60udz.png)
=
![( (t - 3 + 4)/(4))/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vd0n0nbjcgu1up0zahlhny07tw0ts8jykf.png)
=
Answer for (c):
=
![(t + 1)/(8)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/dmi2ik071lge1cd9t1m2qcia2hk55doc8s.png)
(d)
h(g(t)) = h(2t - 1) = 4(2t - 1) + 3 = 8t - 4 + 3 = 8t - 1
Answer for (d): h(g(t)) = 8t - 1
(e)
h(g(t)) = 8t - 1
y = 8 t - 1
t = 8y - 1
t + 1 = 8y
![(t + 1)/(8)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/dmi2ik071lge1cd9t1m2qcia2hk55doc8s.png)
= y
Answer for (e): inverse of h(g(t)) =